Analysis of the Relationship Between the Quality of Academic Service and the Behavioural Intentions of University Students - Šereš, Laslo; Lukić, Nemanja; Rodić Lukić, Vesna (Industrija, 2019)
This paper examines whether the behavioural intentions of students are driven by the quality of services provided by faculty management, academic and administrative staff. The sample included 517 students from the University of Novi Sad, Serbia. In order to investigate the relationship between academic service quality and behavioural intentions, hierarchical multiple regression analysis (HMRA) was conducted. Results of HMRA have shown that approachability and support of academic staff and support of faculty management have both statistically significant relation to behavioural intentions of students. The findings of this research study suggest that the improvement of the academic service quality might foster students’ behavioural intentions.